Edukasi Pedoman Makan “Isi Piringku” untuk Gizi Seimbang pada Balita - Pusmaika, Rangga; Novfrida, Yizri; Nurbayani, Resita (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Toddlers are very vulnerable to nutritional problems. Malnutrition or stunting in Banten in 2022 is 20%, not yet reaching the 2024 RPJMN target of 14%. One way to prevent malnutrition for toddlers is by increasing the knowledge of mothers or caregivers regarding balanced nutrition and eating guidelines. The aim of this community service is expected to provide education to mothers in providing food to toddlers with balanced nutrition in each portion of their meal. This community service method is through outreach by delivering material and direct interaction, using leaflets, posters and flip sheets. The activity was carried out at Posyandu Anggrek 2 in the Cipondoh Tangerang Community Health Center Working Area for 21 mothers who had toddlers. The results show that the majority of mothers of toddlers have attended nutritional guideline education but still need ongoing information to optimize the provision of balanced nutrition to their toddlers. Education is emphasized on the menu for each item on my plate according to the child's age. After the education was carried out, the knowledge of mothers of toddlers increased, marked by the ability to answer post-counseling evaluation questions